The Impact of Inclusive Service Experience on Social Identity and Brand Loyalty: Empirical Study of Inclusive Cafés in Urban Indonesia - Dea Ananda Tiaranurlaisya; Andi Azhar; Yu-Te Tu; Yinghuei Chen (Journal of Economics and Management Scienties, 2026)
This study examines the influence of inclusive service experiences on the formation of social identity and consumer brand loyalty at the inclusive cafe Sunyi Coffee in the context of urban Indonesian society. Based on Social Identity Theory and the concept of inclusive service, this study uses a descriptive qualitative approach with an interpretative paradigm. Data were collected through bold semi-structured interviews with seven participants consisting of customers and members of the disabled community, selected using a snowball sampling technique until data saturation was achieved. Data analysis was conducted using NVivo 12 through the stages of open coding, axial coding, and selective coding, and supported by visualizations in the form of word clouds, cluster analysis, tree maps, and matrix coding. The results identified six main themes: inclusive service systems (recruitment of staff with disabilities and use of sign language), service experiences (educational and reflective), cafe appeal, interest in inclusive concepts, social impact, and social values ​​(equality and empathy). The findings indicate that inclusive service experiences encourage the formation of pro-inclusion social identities and increase value-based brand loyalty through social resonance, not solely functional aspects. Theoretically, this research enriches the literature on inclusive services with the Indonesian narrative context; practically, it offers guidance for social businesses to integrate inclusivity into socio-economic shift strategies.